A refração na tradução e na retradução dos hinos da Harpa Cristã - Razzia, Karine (2023)
This qualitative research starts from the premise that the translation and the retranslation of the hymns of the congregational hymnbook Christian Harp (Harpa Cristã) are refracted by the spectrum of Pentecostal theology, and aims to demonstrate to what extent the deviations in the translation/retranslation of the hymns of The Christian Harp from their source hymns are the result of translation difficulties or refraction by Pentecostal theology, and how much such changes affect inherent principles of song translation such as singability, sense, naturalness, rhythm, and rhyme. Therefore, this research describes the Pentecostal theological spectrum and analyzes the translation of four hymns from Christian Harp (2011), contrasting them with their originals in English and, in the case of a retranslated hymn, comparing it with the translation in the precursor hymnal, Psalms and Hymns (Salmos e Hinos). The analysis is supported by the theoretical-methodological approach of refraction and manipulation (LEFEVERE, 1992 and 2012), and the Pentathlon Theory for song translation (LOW, 2005 and 2017) and considers the intersection between song lyrics and poems (TATIT, 1996 and 2004; GOLDSTEIN, 2005; BRITTO, 2008b, 2012, and 2019), among others. Regarding the results obtained, it was confirmed that refraction affects both semantic and formal aspects of the translated/retranslated hymns and, to a greater or lesser extent, all the principles inherent to the song translation, so that singability, rhythm and rhyme are taken as priorities by the Pentecostal translator, while naturalness and sense assume a secondary position, with sense being a special case due to the nature of the commitment of the Pentecostal translator/retranslator